Ankyloglossia severity in infants: maternal pain, self-efficacy, and functional aspects of breastfeeding - Christyann Lima Campos Batista; Alex Luiz Pozzobon Pereira (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To analyze functional aspects of breastfeeding, self-efficacy, and pain reported by mothers during breastfeeding, in newborns with severe and mild ankyloglossia. Methods: This is an observational study, carried out with 81 babies with ankyloglossia, assessed by the Bristol Tongue Assessment Tool (severe: scores 0-3; mild: scores 4-6) nested in a cohort carried out at the University Hospital of the Federal University of Maranhão, São Luis, Brazil. The functional aspects of breastfeeding were analyzed using the Breastfeeding Observation Form of the United Nations Children's Fund (BOF-UNICEF) and the LATCH Scoring System. Breastfeeding self-efficacy was measured using the Breastfeeding Self-Efficacy Scale - Short-Form. Pain indicators were evaluated by the Short-Form McGill Pain Questionnaire. The significance level adopted was 5%. Results: Maternal age was 26.7±0.8 years, and 64.2% reported high school education. Most babies were male (67.9%), and the birth weight was 3232±60g. A significant association was detected in the sucking aspect evaluated by the BOF-UNICEF [β=0.22 (95%CI 0.07; 0.73), p-value=0.013]. However, the groups did not differ in the assessment of breastfeeding performed by the LATCH scale. The groups had no differences in the assessment of breastfeeding self-efficacy reported by mothers, and in pain scores. Conclusions: Despite the observation of sucking difficulty in infants with severe ankyloglossia., the quality of breastfeeding in general, maternal pain, and self-efficacy reported by mothers do not differ when compared with infants with mild ankyloglossia. Therefore, the severity of ankyloglossia seems not to affect the breastfeeding indicators.